A mobilidade interna na Ordem de Avis : (séc. XII-XIV) - Cunha, Maria Cristina Almeida e (2014)
Building upon information provided to us by the specific documentation of the Military Order of Avis, by the chronicles of the kings of Portugal, by the royal diplomas and by other sundry acts, we sought to reflect upon the knights’ mobility, using as a starting point some references that witness the presence of the Master or the knights of Avis in different points of the Portuguese kingdom and abroad, namely in the general chapter of the Order of Calatrava, upon which the Portuguese militia depended.